Student Entrepreneurship Coaching Using the Smart Entrepreneur Model (SEM) For Strengthening Entrepreneurial Character in The Digital Era - Kusmayadi, Iwan; Bagis, Abdul Azis; Burhanuddin, Burhanuddin; Suprayetno, Djoko; Dakwah, Muhammad Mujahid; Wardani, Laila (Unram Journal of Community Service, 2025)
Student Entrepreneurship Coaching Program with the Smart Entrepreneurial Model (SEM) is designed to strengthen students' entrepreneurial character through an integrated approach. The primary goal of this program is to develop students with an innovative, resilient, and adaptive entrepreneurial mindset, enabling them to respond to market changes and global economic challenges. The urgency of this program lies in the pressing need to create a young generation prepared to face economic disruptions, particularly in the digital era and during industrial transformation. Students, as future entrepreneurs, require a solid entrepreneurial character to take calculated risks, communicate effectively, and manage sustainable businesses. The stages of building entrepreneurial character through SEM include: Phase 1: Pre-test (Psychometric testing); Phase 2: Participant classification and SWOT analysis; Phase 3: Workshops; Phase 4: monitoring and mentoring. The coaching activities based on the Smart Entrepreneurial Model (SEM) have demonstrated a positive impact on shaping students' entrepreneurial character. This program successfully enhances students' growth mindset, communication skills, leadership abilities, and strategic analysis capabilities through a combination of training, business simulations, role-playing, and mentoring